Central Role of Macrophages and Nucleic Acid Release in Myasthenia Gravis Thymus. Issue 4 (25th January 2023) - Payet, Cloé A.; You, Axel; Fayet, Odessa‐Maud; Hemery, Edouard; Truffault, Frederique; Bondet, Vincent; Duffy, Darragh; Michel, Frédérique; Fadel, Elie; Guihaire, Julien; Demeret, Sophie; Berrih‐Aknin, Sonia; et al.
Abstract : Objective: Myasthenia gravis (MG) is a neuromuscular disease mediated by antibodies against the acetylcholine receptor (AChR). The thymus plays a primary role in AChR‐MG and is characterized by a type I interferon (IFN) signature linked to IFN‐β. We investigated if AChR‐MG was characterized by an IFN‐I signature in the blood, and further investigated the chronic thymic IFN‐I signature. Methods: Serum levels of IFN‐β and IFN‐α subtypes, and mRNA expression for IFN‐I subtypes and IFN‐stimulated genes in peripheral mononuclear blood cells (PBMCs) were analyzed. The contribution of endogenous nucleic acids in thymic expression of IFN‐I subtypes was investigated in human thymic epithelial cell cultures and the mouse thymus. By immunohistochemistry, thymic CD68 + and CD163 + macrophages were analyzed in AChR‐MG. To investigate the impact of a decrease in thymic macrophages, mice were treated with an anti‐CSF1R antibody. Results: No IFN‐I signature was observed in the periphery emphasizing that the IFN‐I signature is restricted to the MG thymus. Molecules mimicking endogenous dsDNA signalization (Poly(dA:dT) and 2′3′‐cGAMP), or dexamethasone‐induced necrotic thymocytes increased IFN‐β and α‐AChR expression by thymic epithelial cells, and in the mouse thymus. A significant decrease in thymic macrophages was demonstrated in AChR‐MG. In mice, a decrease in thymic macrophages led to an increase of necrotic thymocytes associated with IFN‐β and α‐AChR expression. Interpretation: These results suggest that the decrease of thymic macrophages in AChR‐MG impairs the elimination of apoptotic thymocytes favoring the release of endogenous nucleic acids from necrotic thymocytes. In this inflammatory context, thymic epithelial cells may overexpress IFN‐β, which specifically induces α‐AChR, resulting in self‐sensitization and thymic changes leading to AChR‐MG. ANN NEUROL 2023;93:643–654